Competitive canalization of PIN-dependent auxin flow from axillary buds controls pea bud outgrowth - Balla, Jozef; Kalousek, Petr; Reinöhl, Vilém; Friml, Jiří; Procházka, Stanislav (The Plant journal, 2011)
Shoot branching is one of the major determinants of plant architecture. Polar auxin transport in stems is necessary for the control of bud outgrowth by a dominant apex. Here, we show that following decapitation in pea (Pisum sativum L.), the axillary buds establish directional auxin export by subcellular polarization of PIN auxin transporters. Apical auxin application on the decapitated stem prevents this PIN polarization and canalization of laterally applied auxin. These results support a model in which the apical and lateral auxin sources compete for primary channels of auxin transport in the stem to control the outgrowth of axillary buds.
Keywords: rostlinné proteiny; stonky rostlin; Plant Proteins; hrách setý; Indoleacetic Acids; regulátory růstu rostlin; Plant Stems; kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Plant Growth Regulators; Pisum sativum